The Effect of Tapioca Flour and Bogor Taro Flour (Colocasia esculenta L. Schott) Formulations on the Chemical, Physical, and Sensory Characteristics of Catfish Sausage (Pangasius hypophtalmus) - Amelia, Leona; Astuti, Sussi; Fadhallah, Esa Ghanim; Koesoemawardani, Dyah (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
This study was aimed to determine the effect of tapioca flour and Bogor taro flour formulation on the chemical, physical, and sensory characteristics of catfish sausage and to determine the best formulation. This study was arranged in a Randomized Complete Group Design (RCGD) with a single factor of tapioca flour and Bogor taro flour formulation with 6 treatments P1 (100%:0%), P2 (80%:20%), P3 (60%:40%), P4 (40%:60%), P5 (20%:80%), and P6 (0%:100%) with 4 replications. Data were tested for equality of variance with Barlett's test and data saturation with Tuckey's test. The data were analyzed for variance to determine the effect between treatments, then further analyzed using the HSD test at the 5% level. The results showed that the formulation of tapioca flour and Bogor taro flour had a very significant on water content, ash content, hardness, springiness, cohesiveness, appearance, and overall acceptance but no effect on the taste and aroma of catfish sausage. P5 was the best treatment with a water content of 52.08%, ash content of 1.55%, hardness of 270.75 gf, springiness of 10.03 mm, cohesiveness of 0.83, appearance of 2.93 (slightly dull), taste of 3.87 (typical of fish), aroma of 3.87 (typical of fish), overall acceptance of 3.88 (like), protein content of 15.61%, and fat content of 4.29%.